Post-translational modifications of Ataxin-3, the protein involved in Machado-Joseph disease - Matos, Carlos (2009)
Dissertação de mestrado em Biologia Celular e Molecular apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra